Elementary School Teachers' Skills in Integrating STEM Education - Siregar, Nur Choiro; Warsito, Warsito; Rosli, Roslinda; Haswati, Desty; Gumilar, Aris (Southeast Asian Mathematics Education Journal, 2024)
Integrating science, technology, engineering, and mathematics (STEM) education is the principal capital to improve the nation's economic dignity. Students' STEM abilities must be different from the role of teachers as facilitators in the learning process at school. The ability of elementary school teachers to apply STEM approaches is critical, especially in mathematics and natural sciences (IPA) studies. The study aims to identify how elementary school teachers are integrating STEM approaches. We used a qualitative case study research method, conducting in-depth interviews with two math teachers and two science teachers from the city and the village. The findings suggest differences in teachers' ability to apply STEM approaches during classroom instruction. Three aspects affect this difference: (1) lack of teacher professional development (training, seminars, or workshops); (2) facilities for obtaining information (equipment such as laboratories and computers); and (3)  different abilities of students (intellectual intelligence). There are differences in the ability of teachers in urban and rural areas to implement STEM approaches. Teachers who teach in villages have limited knowledge of integrated STEM; internal and external factors greatly influence the differences. Therefore, policymakers must undertake more programs and activities to develop their ability to implement STEM approaches. We suggest further research to explore the factors that affect teachers' ability to integrate STEM. We discuss the limitations and implications of this study.